Exergames as a rehabilitation tool to enhance the upper limbs functionality and performance in chronic stroke survivors: a preliminary study - Vismara, Luca; Ferraris, Claudia; Amprimo, Gianluca; Pettiti, Giuseppe; Buffone, Francesca; Tarantino, Andrea Gianmaria; Mauro, Alessandro; Priano, Lorenzo (Frontiers in Neurology, 2024)
Introduction Post-stroke hemiplegia commonly occurs in stroke survivors, negatively impacting the quality of life. Despite the benefits of initial specific post-acute treatments at the hospitals, motor functions, and physical mobility need to be constantly stimulated to avoid regression and subsequent hospitalizations for further rehabilitation treatments. Method This preliminary study proposes using gamified tasks in a virtual environment to stimulate and maintain upper limb mobility through a single RGB-D camera-based vision system (using Microsoft Azure Kinect DK). This solution is suitable for easy deployment and use in home environments. A cohort of 10 post-stroke subjects attended a 2-week gaming protocol consisting of Lateral Weightlifting (LWL) and Frontal Weightlifting (FWL) gamified tasks and gait as the instrumental evaluation task. Results and discussion Despite its short duration, there were statistically significant results (p < 0.05) between the baseline (T0) and the end of the protocol (TF) for Berg Balance Scale and Time Up-and-Go (9.8 and −12.3%, respectively). LWL and FWL showed significant results for unilateral executions: rate in FWL had an overall improvement of 38.5% (p < 0.001) and 34.9% (p < 0.01) for the paretic and non-paretic arm, respectively; similarly, rate in LWL improved by 19.9% (p < 0.05) for the paretic arm and 29.9% (p < 0.01) for non-paretic arm. Instead, bilateral executions had significant results for rate and speed: considering FWL, there was an improvement in rate with p < 0.01 (31.7% for paretic arm and 37.4% for non-paretic arm), whereas speed improved by 31.2% (p < 0.05) and 41.7% (p < 0.001) for the paretic and non-paretic arm, respectively; likewise, LWL showed improvement in rate with p < 0.001 (29.0% for paretic arm and 27.8% for non-paretic arm) and in speed with 23.6% (p < 0.05) and 23.5% (p < 0.01) for the paretic and non-paretic arms, respectively. No significant results were recorded for gait task, although an overall good improvement was detected for arm swing asymmetry (−22.6%). Hence, this study suggests the potential benefits of continuous stimulation of upper limb function through gamified exercises and performance monitoring over medium-long periods in the home environment, thus facilitating the patient's general mobility in daily activities.